Funding for Postbariatric Body-Contouring (Bariplastic) Surgery in England: A Postcode Lottery. (20th March 2014) - Mukherjee, Samrat; Kamat, Sachin; Adegbola, Samuel; Agrawal, Sanjay
Abstract : Background. With the increase in bariatric surgery in the UK, there has been a substantial increase in patients undergoing massive weight loss (MWL) seeking postbariatric body-contouring (bariplastic) surgery. However, there is a wide variation of availability on the National Health Service (NHS). Aims. To (1) review the funding policies of Primary Care Trusts (PCTs) in England for bariplastic surgery and (2) analyse the number of procedures funded in two consecutive financial years. Methods. We sent out questionnaires to all PCTs in England regarding their funding policies for bariplastic surgery and requested the number of procedures funded in 2008-09 and 2009-10. Findings. 121/147 (82%) PCTs replied to our questionnaires. 73 (60%) excluded all bariplastic procedures. 106/121 (87.6%) PCTs had referral guidelines for plastic surgery. 46/121 (38%) PCTs provided the total number of funded abdominoplasty-apronectomy (A-A) in the two financial years: total number of A-A applicants rose from 393 to 531, but approval for funding fell from 24.2% to 19.6%. Only 3 (2%) PCTs indicated increase in their future spending on bariplastic procedures in the next 5 years, with 67% planning to decrease or unsure about future funding. Conclusion. There exists a postcode lottery for bariplastic surgery in England and we feel the need for guidelines on provision of bariplastic procedures following MWL.